Behavioral and Structural Predictors of Adolescents' Attitudes Towards Voluntary Counseling and Testing (VCT) for HIV in East Java, Indonesia - Jayanti Dian Eka Sari; Fajrinia Putri Rudiansyah; Farah Fadhillah; Yeshita Alifia Yuvianti; Eny Qurniyawati; Suhainizam Bin Muhamad Saliluddin; Muthmainnah Muthmainnah; Annisa Clara Salsabila (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: HIV remains a significant global public health issue, with East Java, Indonesia, contributing 15–20% of the national HIV cases. Voluntary Counseling and Testing (VCT) is a critical strategy for early detection and prevention, yet its uptake among adolescents is influenced by multifaceted factors. This study aimed to identify the determinants of adolescents' attitudes towards VCT for HIV in East Java. Methods: An observational analytic cross-sectional study was conducted from July to December 2024, involving 329 adolescents aged 18–24 years selected through random sampling. Data were collected via a validated online questionnaire assessing demographic, socio-economic, knowledge, psychosocial, and institutional factors. Binary logistic regression analysis was employed to determine significant predictors of VCT attitudes. Results: Nine factors were significantly associated with positive attitudes toward VCT: younger age (OR = 0.81), male gender (OR = 2.34), higher parental income (OR = 1.86), higher HIV-related knowledge (OR = 2.18), better VCT knowledge (OR = 1.72), low-risk sexual activity (OR = 1.95), service availability (OR = 2.48), family support (OR = 1.77), and institutional support (OR = 1.63). Conversely, stigma remained a significant barrier (OR = 0.49). Conclusion: Addressing stigma, enhancing institutional and family support, and improving access to VCT services are crucial for increasing VCT uptake among adolescents. Targeted interventions, including family-based approaches and comprehensive sexual education, are recommended to foster positive attitudes and reduce HIV transmission in East Java.